Perceptions of incest and effects of reality therapy and psychospirituality programs on self-esteem and spiritual well-being of adolescent survivors - Gigantone, Myrna R. (Animo Repository, 2000)
This study explores the survivors' perceptions of incest trauma and the self and the effects of Reality Therapy and Psychospirituality on self-esteem and spiritual well-being of female adolescent incest survivors.Thirty-seven institutionalized survivors were randomly assigned to Reality Therapy, Psychospirituality, and Wait-List control groups. Treatment groups received five consecutive daily sessions that lasted from one and a half to two hours. The Self-Esteem Inventory and Spiritual Well-Being Scale data were subjected to ANOVA and Scheffe tests at p .05.Results showed that perceptions of incest trauma centered on betrayal, powerlessness, stigmatization, and traumatic sexualization. Self perceptions were negative and distorted. Particularly, desires focused on reuniting with the family. Perceived program gains complemented the findings on Self-Esteem and Spiritual Well-Being.The findings revealed that Reality Therapy and Psychospirituality programs effectively enhanced self-esteem, and spiritual and existential well-being of adolescent survivors. Reality Therapy significantly improved religious well-being, whereas Psychospirituality did not. The control group had no change. The interventions proved to be relevant tools in counseling this population. However, to establish further sequelae of incest, more investigation is needed for a larger sample size, longer term, with enclosures of other demographic variables on institutionalization, and other populations. Likewise, to establish a theory based on the spiritual well-being along with Filipino theocentricity and Modelling faith among adolescents, more examinations are needed. Moreover, training for caregivers and development of instrument for accurate assessment of incest trauma need to be addressed.